1997
DOI: 10.1103/physrevb.56.7751
|View full text |Cite
|
Sign up to set email alerts
|

Concentric carbon structures

Abstract: We develop a topological explanation of turbostratic stacking and short-range order in multishell nanotubes and fullerene onions through the analysis of steric constraints. A proposed nanotube structure gives good Rietveld x-ray-diffraction refinement of well-annealed samples. We show that each layer in the nanotubes has preferentially a left or right unique helix and stable onions a highly distorted hexagonal array with constant interlayer spacing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The MW (or concentric) [81] nanotubes and nano-onions represent 'radial superlattices' as opposed to the usual 'translational superlattices'. Nanocones are also known to be MW.…”
Section: Complex Geometries and Higher Genus Topological Structuresmentioning
confidence: 99%
“…The MW (or concentric) [81] nanotubes and nano-onions represent 'radial superlattices' as opposed to the usual 'translational superlattices'. Nanocones are also known to be MW.…”
Section: Complex Geometries and Higher Genus Topological Structuresmentioning
confidence: 99%
“…The repeated observations of spherical onion shells as opposed to the predicted Goldberg polyhedra with protrusions along and around the pentagonal defects [5][6][7] have warranted an explanation. Some authors [8,9] have provided results from topological arguments to show that the spherical shell structure is more stable. The formation of closed carbon cages in a cluster-forming environment has been extensively studied [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, non-equal peak breaths were also observed in the low resolution x-ray diffraction (XRD) data from the existing literature [11,[17][18][19][20], and from a recent neutron diffraction experiment [21], where the (004) peaks were found to be wider than (002). Although this could also be attributed to the lattice distortion, it produces a much higher layer number [19].…”
Section: Resultsmentioning
confidence: 69%
“…In some cases the sample purity was about 60% [19]. Although most of them found no strong (101) peak, due presumably to the expected misalignment between the graphite layers, the works of Pasqualini [20] and Burian et al [21] suggested that it is possible to have lateral correlation. Therefore, it is likely that they exist in the samples of high purity.…”
Section: Resultsmentioning
confidence: 97%